Clinical utility of circulating tumor DNA for early detection of recurrence after curative hepatectomy in patients with colorectal cancer with liver metastases: A prospective observational study protocol (CASSIOPEIA) - Akira Inoue; Yoshihiro Morimoto; Yujiro Nishizawa; Masahiro Hashimoto; Yuki Ozato; Kenta Furukawa; Masashi Hirota; Yasuhiro Miyazaki; Akira Tomokuni; Masaaki Motoori; Kazumasa Fujitani (PLoS ONE, 2025)
Colorectal cancer (CRC) with liver-only metastases remains a significant clinical challenge owing to its high recurrence rate, even after curative hepatectomy. Despite advancements in surgical techniques and systemic therapies, identifying patients at elevated risk of recurrence is crucial for optimizing long-term outcomes. Circulating tumor DNA (ctDNA) is a biomarker for minimal residual disease and recurrence risk assessment. We hypothesize that plasma-only ctDNA assays using the Plasma-Safe-SeqS platform can enable early recurrence detection and guide postoperative management, including adjuvant chemotherapy. This single-center, prospective observational study will enroll 10 patients with histologically confirmed CRC and liver-only metastases undergoing curative hepatectomy. Plasma samples are collected preoperatively and at predefined intervals postoperatively (4, 12, 24, 36, and 48 weeks) to monitor ctDNA levels using a highly sensitive 14-gene panel designed to detect tumor-specific mutations. Mutant allele frequencies as low as 0.1% are detected using the Plasma-Safe-SeqS platform. The primary endpoint is the interval between ctDNA detection and clinically confirmed recurrence. The secondary endpoints include mutation concordance between pre- and postoperative samples, 3-year disease-free survival, 5-year overall survival, and correlations with clinicopathological features. Kaplan–Meier estimates and Cox proportional hazards models are used for statistical analyses. To our knowledge, this is the first study to utilize a 14-gene panel with Plasma-Safe-SeqS technology for ctDNA analysis in patients with CRC liver metastases following curative hepatectomy. By eliminating the need for tumor tissue, this plasma-only approach simplifies diagnostics and mitigates logistical barriers, including prolonged turnaround times associated with tumor-informed assays. We aim to validate ctDNA as a reliable biomarker for early recurrence detection. Furthermore, we may provide valuable insights into optimizing adjuvant chemotherapy strategies by identifying high-risk patients who may benefit from treatment while sparing low-risk patients from unnecessary toxicity. These findings may advance personalized postoperative care and enhance long-term outcomes in this patient population. Trial registration The study is registered in accordance with the International Committee of Medical Journal Editors (ICMJE) guidelines under the University Hospital Medical Information Network Clinical Trials Registry (UMIN-CTR). The registry name is UMIN-CTR. The registration number is UMIN000057128. Trial details are available upon request.